A multiplexed phospholipid membrane platform for curvature sensitive protein screening. Issue 29 (16th July 2021) - Berganza, Eider; Ebrahimkutty, Mirsana P.; Vasantham, Srivatsan K.; Zhong, Chunting; Wunsch, Alexander; Navarrete, Alexander; Galic, Milos; Hirtz, Michael
Abstract : Nanoscale membrane deformations are believed to act as signaling hubs that combine geometry and lipid composition. We propose an in vitro platform for curvature sensitive protein screening using nanoparticles with phospholipid patterned on top. Abstract : The curvature of lipid membranes plays a key role in many relevant biological processes such as membrane trafficking, vesicular budding and host–virus interactions. In vitro studies on the membrane curvature of simplified biomimetic models in the nanometer range are challenging, due to their complicated nanofabrication processes. In this work, we propose a simple and low-cost platform for curvature sensitive protein screening, prepared through scanning probe lithography (SPL) methods, where lipid bilayer patches of different compositions can be multiplexed onto substrate areas with tailored local curvature. The curvature is imposed by anchoring nanoparticles of the desired size to the substrate prior to lithography. As a proof of principle, we demonstrate that a positive curvature membrane sensitive protein derived from the BAR domain of Nadrin2 binds selectively to lipid patches patterned on substrate areas coated with 100 nm nanoparticles. The platform opens up a path for screening curvature-dependent protein–membrane interaction studies by providing a flexible and easy to prepare substrate with control over lipid composition and membrane curvature.